Ser Deficiente, Ser Envelhescente, Ser Desejante - Prumes, Cristiane Pasqua (2007)
Simultaneously with the growth, in Brazil, of the number of elderly people, an increase in the life expectancy of the disabled has been observed. Consequently, social issues inherent in every individual emerge. Among them, sexuality, the theme of the present work, which aims to understand the feelings related to the sexuality of individuals suffering from motor and intellectual disability. The qualitative approach with open-ended interviews was used. Four disabled individuals residing in the city of São Paulo were heard. The mother of a disabled and a health professional also gave their opinions concerning the reality portrayed here. In conclusion, although the theme of social inclusion has been exhaustively debated, the sexuality of disabled individuals is pervaded by prejudice, and the institutions and professionals that have been prepared to work with this segment of the population are included as the origin of the prejudice. Due to this, the disabled feel even more deprived of the right to fully exercise their citizenship. Joining technical experience and the capacity for dialog and shelter, helping the individual with his several needs, is also health promotion